The anti-tumor drug 2-hydroxyoleic acid regulates the oncogenic potassium channel Kv10.1 - Rita Morán-Zendejas; Aldo A. Rodríguez-Menchaca (Beni-Suef University Journal of Basic and Applied Sciences, 2023)
Abstract Background 2-hydroxyoleic acid (2OHOA) is a synthetic fatty acid with antitumor properties that alters membrane composition and structure, which in turn influences the functioning of membrane proteins and cell signaling. In this study, we propose a novel antitumoral mechanism of 2OHOA accomplished through the regulation of Kv10.1 channels. We evaluated the effects of 2OHOA on Kv10.1 channels expressed in HEK-293 cells by using electrophysiological techniques and a cell proliferation assay. Results 2OHOA increased Kv10.1 channel currents in a voltage-dependent manner, shifted its conductance-voltage relationship towards negative potentials, and accelerated its activation kinetics. Moreover, 2OHOA reduced proliferation of cells that exogenously (HEK-293) and endogenously (MCF-7) expressed Kv10.1 channels. It is worth noting that the antiproliferative effect of 2OHOA was maintained in HEK-293 cells expressing a non-conducting mutant of Kv10.1 channel (Kv10.1-F456A), while it did not affect HEK-293 cells not expressing Kv10.1 channels, suggesting that 2OHOA interferes with a non-conducting function of Kv10.1 channels involved in cell proliferation. Finally, we found that 2OHOA can act synergistically with astemizole, a Kv10.1 channel blocker, to decrease cell proliferation more efficiently. Conclusion Our data suggest that 2OHOA decreases cell proliferation, at least in part, by regulating Kv10.1 channels.